(In)formality: the meshwork of water service provisioning. (3rd December 2014) - Schwartz, Klaas; Tutusaus Luque, Mireia; Rusca, Maria; Ahlers, Rhodante
Abstract : Cities in developing countries have for many decades been characterized by the co‐existence of different service provision modalities. These modalities usually include a formal water utility and an array of small‐scale private or community‐based service providers. In recent years, the topic of informality in water provisioning has been subject to an upsurge in interest of both policy makers and academics. Frequently, literature on the topic distinguishes between informal providers and formal providers suggesting that a provider belongs to either a formal or informal domain. By highlighting the infrastructure, financing, and regulatory institutions of small‐scale service provisioning in Greater Maputo, Mozambique, this article illustrates how informality and formality are interdependent and permeate throughout the water provisioning process creating a meshwork of service provisioning. Actors involved in service provisioning embody multiple identities and use these identities in various sites of governance in order to develop their water business. By adopting this approach to informality, it becomes impossible to distinguish convincingly between formal and informal providers. Instead, it leads to a focus on water provisioning rather than providers, in which informality and formality traverse through the service provision process. WIREs Water 2015, 2:31–36. doi: 10.1002/wat2.1056 This article is categorized under: Engineering Water > Planning Water Human Water > Water Governance